210 Evaluation of the Effects of Wood-Sourced Biochar as a Feedlot Pen Surface Amendment on Manure Nutrient Capture. (12th April 2022) - Sperber, Jessica L; Troyer, Braden; Norman, Mitch; McPhillips, Levi J; Watson, Andrea K; Erickson, Galen E
Abstract: Two nutrient mass balance experiments were conducted during winter and summer seasons to evaluate the effects of spreading unprocessed Eastern red cedar biochar onto the feedlot pen surface on manure nutrient capture and cattle performance. A 186-d feedlot finishing experiment was conducted from December to June (WINTER) and a subsequent 153-d feedlot finishing experiment was conducted from June to November (SUMMER). The WINTER experiment evaluated 3 treatments, including biochar spread to the pen surface during the feeding period (24 kg/steer; 10 steers per pen), hydrated lime spread to pen surface at end of feeding period (31 kg/steer), and control (no treatment applied). The SUMMER experiment evaluated biochar treatment (31 kg/steer; 8 steers per pen) against control. There was no difference in N and P intake, retention, or excretion ( P ≥ 0.38) between WINTER treatments. Steer performance ( P ≥ 0.10) and carcass characteristics ( P ≥ 0.50) were not impacted by pen treatment in WINTER. Nitrogen and P intake and excretion ( P ≥ 0.35) were similar between treatments in SUMMER and retention of N and P was significantly greater for the biochar treatment ( P = 0.04) due to greater ADG. There was no difference in DMI ( P = 0.48) in SUMMER, steers on biochar pen treatment had heavier HCW and increased ADG ( P = 0.05), resulting in improved feed efficiency ( P = 0.08). In both experiments, biochar addition to the pen surface tended ( P = 0.07) to increase manure N as a percent of manure DM, but this increase in N concentration did not impact kg of N removed from the feedlot pens ( P ≥ 0.15) or N losses ( P ≥ 0.68). The addition of unprocessed red cedar biochar to the feedlot pen surface did not improve manure nutrient capture of N or P and did not reduce N losses associated with soil-based feedlot pens.